Rhinoplasty with Cartilage and Alloplastic Materials, Nasal SMAS Management in Asian Rhinoplasty, Contracture Classification, and Secondary Rhinoplasty with Contracture - Kim, Yong Kyu (Semin Plast Surg, 2015)
Rhinoplasty for Asians is quite different from that of Westerners. Most Asians desire a raised nasal bridge with a projected nasal tip, similar to that of Westerners. Nevertheless, most Asian nasal bones, and upper and lower lateral cartilages are inadequately developed. This largely necessitates the use of a nasal alloplastic material such as a silicone implant, most frequently utilized in nasal cosmetic surgery for Asians. Shaping of the silicone implant is rather easy and its removal is also simple, in the case of a complication or undesired result. The disadvantage of a nasal silicone implant, like that of silicone implants of the breast, is the fibrous capsular formation, which may lead to capsular contracture. The frequently employed types of nasal silicone implant include (1) the boat type in which the silicone implant descends down to the nasal tip, (2) the L-shape in which the silicone implant further extends to the anterior nasal spine (ANS) after passing the tip, and (3) the three-quarter type for which the silicone implant extends down to the upper lateral cartilage. In conjunction with the silicone implant, the cartilages of the ear and the nasal septum are commonly used to create or lengthen tip projection. Asians generally have cartilage with inadequate anatomical development. Instead, they often have an anatomically thick fibrous fatty layer including underdeveloped superficial musculoaponeurotic system (SMAS). Patients with a thick fibrous tissue layer have a bulbous tip. This nasal tip is the area where severe capsular contracture occurs after insertion of a silicone implant. It is imperative that the surgeon properly understands the nasal anatomical characteristics of Asians, and selects an appropriate implant together with a suitable donor cartilage to attain a safe and aesthetically pleasing nose. The same principle should apply to reoperation cases; the fibrofatty layer of SMAS along with the capsular contracture must be removed or released to gain a sufficient soft tissue volume. This provides further stability to the cartilage framework.